Parenteral nutrition: ethical and legal considerations. Issue 964 (3rd February 2006) - Sayers, G M; Lloyd, D A J; Gabe, S M
Abstract : Parenteral nutrition is an expensive therapeutic modality that is used to treat patients with intestinal failure. The benefit it offers in terms of life prolongation needs to be weighed against its risks and burdens. Through the use of descriptive clinical vignettes, this article illustrates the ethical and legal principles that underpin decisions to administer and, more importantly, to withhold or withdraw parenteral nutrition.